Urology services in a tertiary hospital: continuing work during the COVID-19 Movement Control Order in Malaysia - Khor, Vincent; Sidhu, Simran; Muhammad Afiq, Mohd Faizal Ong; Pushpanathan, Mugialan; Fahmy, Omar; Khairul Asri, Mohd Ghani; Azli, Saiful; Lee, Christopher Kheng Siang (Lippincott Williams and Wilkins, 2022)
Severe acute respiratory syndrome coronavirus 2, also known as coronavirus disease 2019 (COVID-19), has spread rapidly around the globe like bush fire. This outbreak was declared a pandemic by the World Health Organization on 11 March 2020. It is an unprecedented global health crisis, a century after the great influenza pandemic (Spanish Flu) occurred in 1918.